2002
DOI: 10.1099/00207713-52-3-861
|View full text |Cite
|
Sign up to set email alerts
|

The cpcB-cpcA locus as a tool for the genetic characterization of the genus Arthrospira (Cyanobacteria): evidence for horizontal transfer.

Abstract: To investigate the genetic diversity of the genus Arthrospira and to compare it with other cyanobacteria, sequences of 670 nt from the phycocyanin operon were determined for 23 natural, cultivated or commercial strains of Arthrospira and compared with sequences from 20 other non-Arthrospira cyanobacterial strains. The sequenced DNA fragment comprises the last 255 nt of cpcB, the cpcB-cpcA spacer and the first 304 nt of cpcA. The resulting phylogenetic tree confirms that the genus Arthrospira is not related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
(24 reference statements)
1
25
0
1
Order By: Relevance
“…Chemotaxonomically, those two genera were also shown to be different, as the Arthrospira fatty acids profile included γ-linolenic acid (GLA), that is absent in Spirulina (Cohen and Vonshak, 1991 ). A phylogenetic study based on the cpcA-cpcB locus revealed that the closest relative of the Arthrospira genus is Planktothrix and that it is not related with Spirulina (Manen and Falquet, 2002 ). The study by Shih et al ( 2013 ) presents an analysis of 74 publicly available and 54 newly sequenced cyanobacterial genomes, including 4 belonging to Arthrospira .…”
Section: Geneticsmentioning
confidence: 99%
“…Chemotaxonomically, those two genera were also shown to be different, as the Arthrospira fatty acids profile included γ-linolenic acid (GLA), that is absent in Spirulina (Cohen and Vonshak, 1991 ). A phylogenetic study based on the cpcA-cpcB locus revealed that the closest relative of the Arthrospira genus is Planktothrix and that it is not related with Spirulina (Manen and Falquet, 2002 ). The study by Shih et al ( 2013 ) presents an analysis of 74 publicly available and 54 newly sequenced cyanobacterial genomes, including 4 belonging to Arthrospira .…”
Section: Geneticsmentioning
confidence: 99%
“…Similarly, cyanobacteria are a global concern for the water industry, due to the presence of bloom forming and/or secondary metabolite producing strains that are a risk to public health or adversely affect the aesthetic quality of the water [2729]. Molecular detection, quantification and identification of cyanobacteria are relatively common [8, 3033], but the numerous primer sets currently available generate amplicons with lengths incompatible with NGS, and/or are specific for only a few members of this phylum [3440]. To overcome these limitations, the present study sought to design taxon-specific primers targeting the cyanobacteria 16S rRNA gene for use with NGS.…”
Section: Introductionmentioning
confidence: 99%
“…Use of cyanobacteria as a food supplement has a long history (Gantar and Svircev 2008) dating back to Antiquity. Referred wrongly to as "Spirulina", Arthrospira Stizenberger 1852, which is in fact more related to Planktothrix and Lyngbia following Manen and Falquet (2002), have already been collected and used by Aztec populations (Ciferri 1983;Pulz and Gross 2004). Even today, malnutrition, especially due to a protein-poor diet is widespread in many parts of the world.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Arthrospira (ex Spirulina) is a non-heterocystous filamentous cyanobacterium, characterised by multicellular, cylindrical and usually screwlike coiled trichomes, inhabiting diverse environments including those of high salinity (Anagnostidis and Komarek 1988;Manen and Falquet 2002). Several strains have been isolated worldwide, and made useful in a variety of fundamental and applied research studies: commercial mass cultures have indeed been developed for the food industry in local areas, but also for alternative biofuel feedstock, skin-care product resources, etc (Ciferri and Tiboni 1985;Belay et al 1996;Fox 1996).…”
Section: Introductionmentioning
confidence: 99%